2009
DOI: 10.1037/a0014227
|View full text |Cite
|
Sign up to set email alerts
|

The Perennial Debate: Nature, Nurture, or Choice? Black and White Americans’ Explanations for Individual Differences

Abstract: This paper examines three common explanations for human characteristics: genes, the environment, and choice. Based on data from a representative sample of White and Black Americans, respondents indicated how much they believed each factor influenced individual differences in athleticism, nurturance, drive, math ability, violence, intelligence, and sexual orientation. Results show that across traits: 1) Black respondents generally favor choice and reject genetic explanations, whereas White respondents indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 40 publications
3
58
2
2
Order By: Relevance
“…Alternatively, it appears that the gender effect may be partially due to the fact that only 15% of White men answered the genes determine race statement correctly, considerably less than any other ethnic/gender group. It is noteworthy that White men may have the most to gain in terms of maintaining their privileged position in the racial/gender social hierarchy by believing that group differences are genetic, and thus, natural and unchangeable [24,38]. However, we found no significant gender difference on the question about genetic similarity within gender, which might have been expected if this were the case.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Alternatively, it appears that the gender effect may be partially due to the fact that only 15% of White men answered the genes determine race statement correctly, considerably less than any other ethnic/gender group. It is noteworthy that White men may have the most to gain in terms of maintaining their privileged position in the racial/gender social hierarchy by believing that group differences are genetic, and thus, natural and unchangeable [24,38]. However, we found no significant gender difference on the question about genetic similarity within gender, which might have been expected if this were the case.…”
Section: Discussioncontrasting
confidence: 56%
“…The primary goal of the larger study was to explore genetic explanations for human traits and their impact on sociopolitical ideologies [38,39]. The surveys were administered by professional interviewers and averaged 40 minutes in length.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps these media reports are common but do not alter public beliefs about more essential racial differences. Finally, research suggests that the public is more inclined to attribute physical and health-related characteristics to genetic factors than outcomes such as talent and success in life (Condit et al 2004; Jayaratne et al 2009; Parrott et al 2005; Singer, Corning, and Lamias 1998); this may limit the extent to which messages about racial differences related to genetics and health will generalize to more general racial differences.…”
Section: Research Strategy and Hypothesesmentioning
confidence: 99%
“…Therefore, our sample may not have had enough men to adequately account for potential gender differences in opinions on genetics and health inequalities. There have been a number of recent discussions about potential gender differences in knowledge and attitudes regarding genetics (Henneman et al 2006;Jayaratne et al 2009). For example, one study reported higher levels of knowledge among women regarding the genetic determination of race (Christensen et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have begun to explore the potential impact of genetic knowledge on views regarding genetics and geneenvironment interactions (Christensen et al 2010;Jayaratne et al 2009;Singer et al 2004). One study for example found that African-American and Latino participants were less likely to utilize genetic services based on a lack of knowledge provided to them through their health care providers (Suther and Kiros 2009).…”
Section: Discussionmentioning
confidence: 99%